A Distributed Implementation Algorithm for Physical Layer Security Based on Untrusted Relay Cooperation and Artificial Noise. Issue 1 (1st February 2014) - Li, Xiangyu; Wang, Xueming; Xu, Xiangyang; Jin, Liang
Abstract : In this letter, we consider a cooperation system with multiple untrusted relays (URs). To keep the transmitted information confidential, we obtain joint channel characteristics (JCCs) through combining the channels from the source to the destination. Then, in the null space of the JCCs, jammers construct artificial noise to confuse URs when the source node broadcasts its data. Through a distributed implementation algorithm, the weight of each node can be obtained from its own channel state information. Simulation results show that high‐level security of the system can be achieved when internal and external eavesdroppers coexist.